Lived religion en theologie: Betekenissen en consequenties van de studie van 'geleefde religie' - Dillen, Annemie (Tijdschrift voor theologie, 2017)
This article discusses a number of characteristics of a ‘lived religion’ approach of the study of religion and/or theology. The author starts by showing in what way ‘lived religion’ is used as an alternative idea and concept instead of the more common approaches. Three different aspects of the term ‘lived religion’ are distinguished. ‘Lived religion’ is discussed as the study of ‘lived’ rather than ‘learned’ religion (1), as an often qualitative empirical approach that will go beyond measuring what religious institutions deem important (2) and as an approach of a lived ‘religion’ and not simply theology or Christian faith (3). This article discusses the relevance of this alternative approach for theology and the study of religion, but it also points out potential pitfalls. Finally, the author discusses the meaning of the concept of ‘lived religion’ for strategical decisions in the church and for the ordinary faithful or the religious seekers. This contribution shows how a stronger focus on the complexity of experience and the hybridity that often characterises religious experience does not merely open up new perspectives in theology and/or the study of religion, but also in ecclesial practice and in the individual experience of seeking, religious people. This results in an appreciation of people and their various different ways of experiencing religion. Within catholic theology too, attention is paid to the diverse ways in which religion is experienced by individuals and groups, but this is often fairly limited. One of the reasons for this is the focus on the doctrinal consequences of any statements by the doctrinal authority. Pope Francis’ attention to the ideas of larger groups of believers and their practices could be an incentive for the study of ‘lived religion’. It must be noted however, that the concept of ‘lived religion’ usually refers to a much wider and more diffuse idea of religion than that which can be found in official church documents. In this way, (catholic) theology is challenged to consider the meaning of this fairly recent trend (the study of ‘lived religion’). This contribution offers some starting points.